Fälle zum Verwaltungsrecht 16 Klausurfälle mit ausführlichen Lösungen - Eisentraut, Nikolas (Carl Grossmann Verlag, 2019)
The present case repertory on administrative law is the first openly licensed case repertory in German jurisprudence. It wants to carry the idea of ​​free educational materials (so-called "Open Educational Resources") into the area of ​​the jurisprudential educational literature as a "lighthouse project" and to encourage imitation. It accompanies the textbook "Administrative Law in the Exam", also published in 2019, and enriches this concrete case study. Administrative Law Cases presents the audit-relevant administrative law on the basis of 16 major cases, which could also be reviewed in exams in this form.The detailed solutions are accompanied by an introduction to the expert review and the examination procedures for the most important application and application types of the VwGO The contents of the open access textbook "Administrative Law in the Exam" can be used to train the practical work with facts in exams with the case repetition The publisher Nikolas Eisentraut is a researcher at the Department of Law of Freie Universität Berlin and Alumni of Wikimedia , the Stifterverband and the Volkswagen Foundation funded Fellow Program Free Knowledge, within the framework of which this Fallrepetitorium has emerged.